Kauniolide synthase is a P450 with unusual hydroxylation and cyclization-elimination activity. Issue 1 (December 2018) - Liu, Qing; Beyraghdar Kashkooli, Arman; Manzano, David; Pateraki, Irini; Richard, Lea; Kolkman, Pim; Lucas, Maria; Guallar, Victor; de Vos, Ric C.H.; Franssen, Maurice; van der Krol, Alexander; Bouwmeester, Harro
Abstract Guaianolides are an important class of sesquiterpene lactones with unique biological and pharmaceutical properties. They have been postulated to be derived from germacranolides, but for years no progress has been made in the elucidation of their biosynthesis that requires an unknown cyclization mechanism. Here we demonstrate the isolation and characterization of a cytochrome P450 from feverfew (Tanacetum parthenium ), kauniolide synthase. Kauniolide synthase catalyses the formation of the guaianolide kauniolide from the germacranolide substrate costunolide. Unlike most cytochrome P450s, kauniolide synthase combines stereoselective hydroxylation of costunolide at the C3 position, with water elimination, cyclization and regioselective deprotonation. This unique mechanism of action is supported by in silico modelling and docking experiments. The full kauniolide biosynthesis pathway is reconstructed in the heterologous hostsNicotiana benthamiana and yeast, paving the way for biotechnological production of guaianolide-type sesquiterpene lactones. Guaianolides are pharmaceutically interesting molecules. Here, the authors isolate the enzyme kauniolide synthase from feverfew, show that it converts constunolide into a guaianolide via an unusual mechanism of action, and reconstruct the full kauniolide biosynthesis pathway in host organisms.